Caracterización zoométrica de cuyes (Cavia porcellus), línea Perú, en la granja APALVE - Laredo - Trujillo Cruzado, Hadehit Yoelinne (2019)
The present study aimed to determine the zoomometric characterization of the population of guinea pigs of the Peru Line; Likewise, its phenotypic and morphological characteristics were identified by observation and quantification: The research was carried out in the Laredo Vision and Empresa-APALVE Agricultural Productive Association, located in the district of Laredo, Province of Trujillo, Department of La Libertad. The data obtained in the investigation were processed using Excel to calculate descriptive statistics and format tables and graphs. It was determined that the guinea pigs are zoomtrically homogeneous with respect to the quantitative variables evaluated, and similar in the qualitative characteristics of the studied Line. The zootechnical characterization of guinea pigs of the company APALVE - Laredo are of high production and productivity.